Fate and Effects of Crude Oil Spilled on Permafrost Terrain. First Year Progress Report. - Collins,C; Deneke,F; Jenkins,T; Johnson,L; McFadden,T (1976)
The long-term effects and ultimate fate of crude oil spilled on permafrost-underlain tundra is the subject of this study. The project involves two experimental oil spills of 2000 gallons (7570 liters) each on 500-sqm test plots near Fairbanks, Alaska. A winter spill, discussed in this report, took place in February 1976. Another spill will take place at the peak of the growing season in the summer. This allows conditions prevailing during these climatic periods to be studied as to their effect on oil spills, and makes it possible to study the reaction of the spilled oil to these temperature extremes. The February spill, designed to simulate a real pipeline leak, was large enough to approach reality while remaining within the limits of logistical capabilities. Monitoring the spill and control plots includes: oil movement, temperature regime, biological effects, microbiological changes, permafrost impact, and chemical degradation of the oil.